Feeder 9 Gas Pipeline Replacement Tunnel – Achieving a world record for pipe insertion of a new gas pipeline within a tunnel beneath the river Humber (UK). Issue 5 (1st October 2021) - Jukes, Simon; Schenk, Stephan
Abstract: Since December 2020, at a pressure of 70 bar, up to 25 % of Britain's gas requirements was flowing through the new Feeder 9 gas pipeline, which installed in a 4.9 km long tunnel 30 m below the River Humber. With the insertion of the new pipeline, the Humber Pipeline Joint Venture (HPT JV), consisting of the companies Porr, Skanska and A. Hak, achieved a major milestone when it was officially recognised as a Guinness World Record for the longest hydraulically‐inserted pipe at 4, 963.7 m long. Replacing the existing pipeline was an absolute necessity due to the shifting river bed which, over the years, had exposed sections of the pipeline threatening the supply to the customers in the UK. The solution adopted by the client, National Grid to provide a long‐term permanent solution, was for the construction of a segmental lined tunnel with an inner diameter of 3.65 m accommodating the new 1050 mm diameter welded steel gas pipe. The tunnel was excavated with a 4.4 m diameter mix shield type TBM. The small diameter together with the length, without intermediate access including a tidal range in the Humber estuary of up to 6.4 m and an overburden on the tunnel of 10 m below the river bed resulted in a number of challenges. The installation of the concrete‐coated steel pipeline was particularly high risk. The individual strings ranging from 595 to 620 m in length and weighing about 850 t, were pushed consecutively into the water‐filled tunnel employing two hydraulic thrusters in just 18 days. Abstract: Feeder 9 Gas Pipeline Replacement Tunnel – Erzielung eines Weltrekords bei der Verlegung einer neuen Gasleitung in einen Tunnel unter dem Fluss Humber (UK) Seit Dezember 2020 strömt bis zu 25 % des britischen Gasbedarfs mit einem Druck von 70 bar durch die neu verlegte Feeder 9 Gasleitung, die in einen 4, 9 km langen Tunnel 30 m unter dem Fluss Humber verläuft. Mit dem Einschieben der Leitung erreichte das Humber Pipeline Joint Venture (HPT JV), bestehend aus den Firmen Porr, Skanska und A. Hak, einen neuen Weltrekord, der offiziell als Guinness‐Weltrekord für das längste hydraulisch eingebrachte Rohr mit 4.963, 7 m anerkannt wurde. Der Austausch der bestehenden Gasleitung war aufgrund eines sich verändernden Flussbetts notwendig, da im Laufe der Jahre Teile der Pipeline durch Erosion infolge der Gezeiten freigespült wurden und damit die Gasversorgung in UK gefährdet war. Der Bauherr National Grid entschied sich für den Bau eines Tübbingtunnels mit 3, 65 m Innendurchmesser zur Aufnahme der Gasleitung mit 1.050 mm Durchmesser zur dauerhaften Absicherung. Der Tunnel wurde mittels Mixschild TBM mit einem Bohrdurchmesser von 4, 4 m aufgefahren. Der relativ kleine Durchmesser in Verbindung mit der großen Länge ohne Zwischenangriff sowie dem Gezeitenhub in der Humbermündung mit bis zu 6, 4 m und einer Überlagerung des Tunnels von 10 m bis zum Flussbett führten zu einer Reihe von Herausforderungen. Besonders anspruchsvoll war auch der Einbau der mit Beton beschichteten Stahlrohrleitung. Die acht einzelnen Stränge von 595 bis 620 m Länge mit einem Gewicht von je ca. 850 t wurden nacheinander mithilfe von zwei hydraulischen Vorschubaggregaten in nur 18 Tagen in den wassergefluteten Tunnel geschoben.